2017
DOI: 10.1097/j.pain.0000000000000907
|View full text |Cite
|
Sign up to set email alerts
|

Sustained improvements in pain, mood, function and opioid use post interdisciplinary pain rehabilitation in patients weaned from high and low dose chronic opioid therapy

Abstract: Increased prescribing of opioids for chronic noncancer pain is associated with significant social costs, including overdose and addiction. In this context, there is interest in interdisciplinary chronic pain rehabilitation programs focusing on self-management and minimizing opioid use. This study examined outcomes of patients weaned from opioids in an ICPRP from 2007 to 2012. Participants included 413 patients on high dose chronic opioid therapy (COT; >100 mg), 528 on low dose COT, and 516 not on opioids (NO).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 68 publications
0
49
0
Order By: Relevance
“…Altogether, these results contribute to explain the renowned lack of efficacy of MOP opioid agonists for the treatment of neuropathic pain (Bian et al, ; Huffman et al, ; Kimura, Obata, & Saito, ; Mao, Price, & Mayer, ; Rashid, Inoue, Toda, & Ueda, ; Wegert et al, ) and suggest the need for searching for alternatives to MOP opioid agonists. The identification of neuropathic pain as a pathological entity aggravated through MOP activity could be relevant to the reduction in the use of opioid drugs and to limit the clinical damage associated with the current opioid crisis (Volkow & McLellan, ).…”
Section: Discussionmentioning
confidence: 85%
“…Altogether, these results contribute to explain the renowned lack of efficacy of MOP opioid agonists for the treatment of neuropathic pain (Bian et al, ; Huffman et al, ; Kimura, Obata, & Saito, ; Mao, Price, & Mayer, ; Rashid, Inoue, Toda, & Ueda, ; Wegert et al, ) and suggest the need for searching for alternatives to MOP opioid agonists. The identification of neuropathic pain as a pathological entity aggravated through MOP activity could be relevant to the reduction in the use of opioid drugs and to limit the clinical damage associated with the current opioid crisis (Volkow & McLellan, ).…”
Section: Discussionmentioning
confidence: 85%
“…Noteworthy, as demonstrated in our study, the groups did not differ regarding opioid dose and pain intensity, which indicated that L‐TOT in some of these patients may be dispensable. In addition, considering the limitations of retrospective designs, there are studies that reviewed patients’ charts and reported improvements on pain, mood and function following interdisciplinary rehabilitation programs for CNCP, which included opioid tapering off or cessation (Murphy et al., ; Cunningham et al., ; Huffman et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, as demonstrated in our study, the groups did not differ regarding opioid dose and pain intensity, which indicated that L-TOT in some of these patients may be dispensable. In addition, considering the limitations of retrospective designs, there are studies that reviewed patients' charts and reported improvements on pain, mood and function following interdisciplinary rehabilitation programs for CNCP, which included opioid tapering off or cessation (Murphy et al, 2013;Cunningham et al, 2016;Huffman et al, 2017). Another aspect of particular note was the fact that 58.3% of patients included in our study achieved stable treatment, which represents a high level of attainment compared to 34.5% of a previous available retrospective report in a similar sample (Schneider and Kirsh, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the absence of such substitutions in among long‐term HCP users is counterintuitive, given that there are many alternative treatments for pain that could take the place of gaps in treatment created by hydrocodone discontinuation. On the other hand, studies of opioid titration among individuals using chronic opioids generally suggest that pain levels remain similar or decrease as opioid doses decline . In addition, in so far as some of the hydrocodone used occurred in settings with an unfavorable risk/benefit balance, the upscheduling may have decreased such use without a commensurate increase in the use of pharmacologic alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies of opioid titration among individuals using chronic opioids generally suggest that pain levels remain similar or decrease as opioid doses decline. [27][28][29][30][31][32][33] In addition, in so far as some of the hydrocodone used occurred in settings with an unfavorable risk/benefit balance, 34 baseline may be an important predictor of a policy's impact. 36 The study, which compared states based on their level of opioid-related legislation, found greater variation in opioid outcomes among states with similar rates of legislation than across states that had different levels of legislation.…”
Section: Discussionmentioning
confidence: 99%